2018
DOI: 10.1002/cphc.201800624
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Basis for 129Xe Hyper‐CEST Signal in TEM‐1 β‐Lactamase

Abstract: Genetically encoded (GE) contrast agents detectable by magnetic resonance imaging (MRI) enable non-invasive visualization of gene expression and cell proliferation at virtually unlimited penetration depths. Using hyperpolarized Xe in combination with chemical exchange saturation transfer, an MR contrast approach known as hyper-CEST, enables ultrasensitive protein detection and biomolecular imaging. GE MRI contrast agents developed to date include nanoscale proteinaceous gas vesicles as well as the monomeric ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…This technique has a potential for many applications since Xe is oen used as a surrogate for O 2 to study gas binding proteins. 38,39 Signicant chemical shis have been observed in such proteins [40][41][42] (with 60-80 ppm downeld shi) or macrocyclic hosts in ternary systems that are of pharmacological interest 43,44 (ca. 100 ppm upeld shi).…”
Section: Relaxivity-derived Xe Exchange Ratesmentioning
confidence: 99%
“…This technique has a potential for many applications since Xe is oen used as a surrogate for O 2 to study gas binding proteins. 38,39 Signicant chemical shis have been observed in such proteins [40][41][42] (with 60-80 ppm downeld shi) or macrocyclic hosts in ternary systems that are of pharmacological interest 43,44 (ca. 100 ppm upeld shi).…”
Section: Relaxivity-derived Xe Exchange Ratesmentioning
confidence: 99%
“…This initial study triggered interest in characterizing the Xe-bla interaction. X-ray crystallography, as well as its combination with protein mutagenesis and MD simulations revealed that bla crystallized as a tetramer with three cavities for Xe atoms (designated as Xe1, Xe2, and Xe3) being identified at similar sites in all four bla molecules [ 419 ]. Unsurprisingly, these include predominantly hydrophobic protein side chains leading to no water occupancy.…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…HyperCEST studies of bla mutants I263A and I279N revealed complete loss of CEST responses. Additional MD simulations and X-ray crystallography for single point mutations (I263A, I263N and I263L) illustrated that these can highly impact Xe access to the cavity and thus alter the achievable CEST contrast [ 421 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…Recently, it was attempted to characterize the Xe-bla interaction through X-ray crystallography, protein mutagenesis combined with X-ray based structural determination, and MD simulations such that the structural basis for the generation of the HyperCEST response can be elucidated. X-ray crystallography of bla indicated that it crystallized as a tetramer, and three Xe atoms (designated as Xe1, Xe2, and Xe3) were observed at similar (binding-)positions in all four bla molecules [164]. These three binding sites are comprised of predominantly hydrophobic protein side chains leading to no water occupancy.…”
Section: Biogenic Nanocarriers For Hypercest Applicationsmentioning
confidence: 99%